2020
DOI: 10.3390/ma13214962
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Structural and Magnetic Properties of Bulk Fe61Co10B20W1Y8−XPtx Alloys through the Partial Substitution of Pt for Y

Abstract: This paper presents the results of an investigation into rapidly quenched Fe-based alloys with the chemical formula: Fe61Co10B20W1Y8−xPtx (where x = 3, 4, 5). In these alloys, a small quantity of Pt was added, and the Y content was reduced concurrently. Samples of the aforementioned alloys were injection-cast in the form of plates with the dimensions: 0.5 mm × 10 mm × 10 mm. The resulting structure was examined using X-ray diffractometry (XRD), Mössbauer spectroscopy and scanning electron microscopy (SEM). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Recently, there have been reports on the preparation and characterization of such ternary Fe-Pt-B alloys, using a plethora of non-equilibrium synthesis methods, to obtain both layered structures, such as thin films and multilayers, and bulk alloys, such as melt spun ribbons [5][6][7]. Magnetic composites of the multilayer type, made of FeB pre-alloy co-doped within FePt deposited films, were studied by Tsai et al [8] Such exchangecoupled hard-soft system have shown a perpendicular anisotropy with a single switching field.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been reports on the preparation and characterization of such ternary Fe-Pt-B alloys, using a plethora of non-equilibrium synthesis methods, to obtain both layered structures, such as thin films and multilayers, and bulk alloys, such as melt spun ribbons [5][6][7]. Magnetic composites of the multilayer type, made of FeB pre-alloy co-doped within FePt deposited films, were studied by Tsai et al [8] Such exchangecoupled hard-soft system have shown a perpendicular anisotropy with a single switching field.…”
Section: Introductionmentioning
confidence: 99%
“…The fe-based amorphous alloys are used as new materials with a special combination of superior chemical [1][2][3], magnetic [4,5] and mechanical properties [6][7][8], which is very important in terms of technology in the last decade. Understanding their mechanical behavior makes them more important for use as advanced engineering materials due to the high strength and low cost of these alloys [9,10].…”
Section: Introductionmentioning
confidence: 99%